DIGITAL-BASED YOUNG ENTREPRENEURSHIP DEVELOPMENT IN INDONESIAN ASSOCIATION OF YOUNG BUSINESSMEN FOR HIGHER EDUCATION IN CENTRAL JAVA - Satria Agung Prabowo; Arditiya Bayu Prasetiyo; Arief Budi Prasetya; Hadi Supratikta (Jurnal Scientia, 2023)
This research is motivated by the increasingly advanced development of science and technology, which has resulted in the replacement of human workers with machine workers. One solution is to increase skills in utilizing digital technology through entrepreneurial organizations. The purpose of this research is first to analyze the management of digital-based young entrepreneur development at HIPMI higher education chapter in. This research method is descriptive qualitative, researchers carry out activities by describing data and facts by finding existing realities and are carried out continuously from the beginning to the end of the study. The results of this study obtained that HIPMI higher education chapter in Central Java has developed its members into digital-based young entrepreneurs, through work programs that have been compiled in the work program syllabus. The conclusions in this study are the management of digital-based young entrepreneur development at HIPMI higher education chapter in Central Java has been fulfilled, namely through the stages of planning, organizing, implementing / activating and supervising